Examining the Vulnerability of the Betawi Language through a Multidisciplinary Approach - Siregar, Iskandarsyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Betawi language, the original language of Jakarta's indigenous population, is currently facing a critical situation due to the rapid progress and changes in the city's social and cultural landscape. This predicament underscores the urgent need for strong and effective strategies to preserve this linguistic heritage. This concern stems from concerns that the extinction of the Betawi language will result in failure to pass on the valuable traditions, technology, cultural norms and customs of the Betawi people to future generations. The loss of such a civilization signals the collapse of a rich and unique cultural heritage. This research was designed to examine the current health and vitality of the Betawi language, using the disciplines of Social Semiotics, Demography and Sociology as the methodological framework. Rather than relying solely on quantitative data, this research uses a qualitative approach to capture particular intricacies, nuances, and preferences regarding language use and meaning. The findings of this research indicate that the Betawi language is more vulnerable today than in the past, and this decline has severe consequences for the Betawi community. Despite these challenges, educational interventions show promise in helping to preserve the language. In the future, it is important to develop a comprehensive strategy for preserving the Betawi language that involves the collaboration of various stakeholders in various sectors.